PREFIXAL REFLEXIVE VERBS - Olga A Grachyova; Polina A Kopylova (RUDN Journal of Language Studies, Semiotics and Semantics, 2017)
The main features of Russian prefixal reflexive verbs, which were made only by prefixal-postfixal and prefixal methods of forming, dissimilar in structure and meaning (620 units) are considered in this article. Defined the degree of activity of functioning prefixes of reflexive verbs, quantitative data ranking of verbs according to the degree of usage of certain prefixes. The article provides a thorough and detailed study of the meanings of reflexive verbs with each specific prefix, gives a complete list of all re-flexive verbs of the above-mentioned ways of founding, identifies prefixes which were semantically marked, and prefixes which were semantically unmarked. It concluded directly proportional to the number of re-flexive verbs with certain prefixes on the number of values the possess. The article applied approaches to the analysis of prefixal reflexive verbs - “from form to meaning” and “from meaning to form”, that allowed to establish between them relations of polyfunctionality, homonymy, isofunctionality, interpreted in the field of prefixes. To understand the specificity of this type of morpheme, the article provides a com-parison of the different prefixes, functioning in the same context, emphasizes the importance of such studies for describing the verbal sign of reccurence.